IMPACT OF VISUAL AND VERBAL SCAFFOLDING ON WEB-BASED PROBLEM SOLUTION PERFORMANCE IN VOCATIONAL SCHOOL STUDENTS - Maria Cleopatra (International Journal of Education, Information Technology, and Others, 2019)
This study aims to determine the impact of differences in visual and verbal scaffolding on the performance of web-based problem solving. A quasi experiment was conducted on 140 high school students in class XII in Bekasi. The visualization tendency of each student was obtained at the beginning of the study. Based on visualization tendency scores, students are divided into two groups namely groups with low and high visualization tendencies. Each group is divided in half and randomly marked one to two lessons, namely visual scaffolding and verbal scaffolding. The eyes on the two lessons are the same. all student performance measured by a problem solving essay task at the end of the lesson. The results of the study showed that the visual scaffolding group outperformed the verbal scaffolding group (F = 22.54, P <.01). By not taking into account a significant degree of tendency. There was no significant impact of interaction between modalities scaffolding and trend level visualization of students. This finding implies that visual scaffolding is an effective strategy that influences the performance of problem solving.